The ascendancy and fall Italian domination in southern Red Sea Arabian During The first half of the twentieth century A.D - الشهراني, سعيد بن علي عبدالله (مجلة دراسات في التاريخ والآثار, 2024)
This paper reviews several theories underlying the ascendancy and fall Italian domination in southern Red Sea during the first half of the twentieth century, by analyzing original sources.Since 1901 There was an agreement and coordination between Italy and England and France on the division of spheres of influence in the region, Italian interests in that district have been emphasized to secure the political and economic influence of Italy in the Yemen and Eritrea. On 1929 a change occurred in Italy's policy when it separated its relations with Yemen and establishing a relationship of friendship and alliance with Ibn Saud, but he to grant the British companies’ concessions in the western coastal region to use the British as a barrier against the augmented Italian threat in the southern part of the Red Sea. In August 1940, when Italy declared war on Britain succeeded British forces eliminated Italian Empire in East Africa, and the Saudi-Italian relations were frozen under British pressure.The analysis hopes to provide findings for future understanding to explore the goals and methods of imperialist countries to control the strategic regions the basin Red Sea as The Italian embraced 's principle that the " keys to the Mediterranean are found in the Red Sea",  the Role Britain in exclusion of Italy from the territories of western and southern Arabia, the Red Sea to protect British interests, and the role Kingdom of Saudi Arabia to confront the imperialist for insurance the road to two Holy Mosques.